LITERATURE REVIEW INDIVIDUAL PERCEPTIONS AND DECISION MAKING: BIBLIOMETRIC ANALYSIS - Ismawati; Sopiah (Bajang Institute, 2022)
One of the ups and downs of realization in the company is a belief and perception in making decisions about the individual himself. Various factors that influence decision making, namely decision making decision privacy , attitude individual , knowledge about risk and protection , trust in others trust in ability for protect information and considerations . In study this for obtain data using analysis bibliometrics . Article data study this collected through the Google Scholar software. The purpose of this study is to provide an overview of the topic